Quality changes in Murta (Ugni molinae) under frozen home storage - Quevedo León, Roberto (2023)
Fruits, especially berries and their processed derivatives have been shown to contain good sources of bioactive compounds, such as vitamin C and phenolic compounds and antioxidant capacity. Frozen storage temperatures of -5, -10, and -15 °C were used to determine the kinetic degradation of vitamin C content, total phenol content, and antioxidant capacity in non-industrial home freezers. The kinetics were satisfactorily fitted to the Weibull model. The rate of degradation of vitamin C in Murta while in frozen storage was notably higher in comparison to that of the total phenol and the antioxidant capacity, respectively. The degradation rate of each component measured, correlated satisfactorily with the Arrhenius law. The arbitrary 70% loss in both vitamin C and antioxidant capacity can place the shelf-life of whole murta in frozen home storage within 240 days and 194 days.